2020
DOI: 10.1007/s00223-020-00680-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived Fracture Risk in the Global Longitudinal Study of Osteoporosis in Women: Its Correlates and Relationship with Bone Microarchitecture

Abstract: The purpose of this study is to examine correlates of self-perceived fracture risk (SPR) and relationships between SPR and subsequent bone density and microarchitecture in the UK arm of the Global Longitudinal Study of Osteoporosis in Women. 3912 women completed baseline questionnaires detailing medical history and SPR; 492 underwent HRpQCT scans of the radius and tibia and DXA scans of total body, hip, femoral neck and lumbar spine a median of 7.5 years later. Correlates of SPR were examined and a cluster ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Roles of trabecular bone micro-structure in determining bone strength and fracture-risk have been convincingly established in histologic studies (Parfitt et al 1983, Kleerekoper et al 1985, Moore et al 1992, Legrand et al 2000, Sornay-Rendu et al 2017, Litwic et al 2020.…”
Section: Introductionmentioning
confidence: 98%
“…Roles of trabecular bone micro-structure in determining bone strength and fracture-risk have been convincingly established in histologic studies (Parfitt et al 1983, Kleerekoper et al 1985, Moore et al 1992, Legrand et al 2000, Sornay-Rendu et al 2017, Litwic et al 2020.…”
Section: Introductionmentioning
confidence: 98%
“…Dual‐energy X‐ray absorptiometry (DXA) computed BMD is clinically used to detect osteoporosis. It is known that BMD explains 60%–70% of the bone's mechanical competence and the remaining is contributed by several other factors such as trabecular bone (Tb) strength and microstructural basis 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…It is known that BMD explains 60%-70% of the bone's mechanical competence and the remaining is contributed by several other factors such as trabecular bone (Tb) strength and microstructural basis. [4][5][6][7] Finite element (FE) analysis (FEA) is widely used to compute Tb mechanical properties from high-resolution three-dimensional (3-D) images. [8][9][10][11][12][13] It has been shown that Tb modulus measures computed from FEA on micro-CT scans highly correlate with experimentally observed values, and often, micro-CT-based FEA is considered a gold-standard method for estimating Tb mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…At the age postmenopause there is an evidence of the risk of osteoporosis and hip fractures in the women. The self-perception osteoporosis results certain behavior like advance medical consultation, bone mineral density screening, medication which may lead to advance health care and improve the bone health [15].…”
Section: Introductionmentioning
confidence: 99%